Heterosis in agriculture - Springer, Nathan M. (Henry Stewart Talks, 2013)
Heterosis, Hybrid vigor of heterozygous off-spring relative to parents, Dominance and over-dominance theories of heterosis, Lessons from heterosis phenotypes, Genomic variation and heterosis, Practical implications of heterosis, Breeding and seed production practices